MOTION Case Studies From Overtourism to Sustainable Tourism - Henriksson, Kristina; Riihihuhta, Jami; Hardiman, Marco; Bretschneider, Jan; Topal, Kalender; Labanauskaite, Daiva; Spiriajevas, Eduardas; Ignasiak-Szulc, Aranka; Makowska, Ewa; Józefowicz, Barbara; Castañeda García, José Alberto; Martín-Rojas, Rodrigo (Laurea-ammattikorkeakoulu, 2023)
The time of the pandemic coincided with much of the lifecycle of the project MOTION, which aimed at combating overtourism with innovating sustainable solutions for SMEs in the tourism industry. SMEs faced a lot of challenges then and still encounter different barriers in their daily lives due to, for example, limited time or financial resources. This publication illustrates ways to develop sustainable services through innovation to inspire readers and actors in the tourism industry to work towards a sustainable future in tourism in the EU. The publication is also suitable for educational purposes, and is useful reading for both educators and students. The case studies generated in Rovaniemi in Finland, Fehmarn and Kiel in Germany, the Curonian Spit in Lithuania, Toruń in Poland, and Granada and Monachil in Spain provide ideas for other businesses in Europe to find their niche in a sustainable future. The project is funded by the Finnish National Agency of the EU for the years 2020–2023.